1995
DOI: 10.3354/meps121053
|View full text |Cite
|
Sign up to set email alerts
|

Influence of zooplankton grazing on free dissolved enzymes in the sea

Abstract: In the Northern Adriatic Sea, extracellular enzymatic activity was measured during a Lagrangian study following a drifting buoy for 40 h. Dissolved free enzymatic activity represented 20 to 70% of total activity depending on the type of enzyme. a-and P-glucosidases exhibited a significantly higher free activity than proteolytic enzymes. In subsequent laboratory experiments we investigated the effect of zooplankton on the free enzyme pool. The 4-step approach included: ( l ) determinatlon of the enzymatic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 32 publications
(46 reference statements)
4
55
1
Order By: Relevance
“…Previous studies from this lake showed indirect evidence of zooplankton control of phytoplankton (PUG-NETTI and BETTINETTI, 1995;CAMMARANO and MANCA, 1997) and protozoa (CALLIERI et al, 1999;BERTONI et al, 2002) during Daphnia peaks. BOCHDANSKY et al (1995) observed similar increase in both dissolved α-and -glucosidase activities with increase in marine copepods in batch experiments. Small changes in bacterial biomass were not sufficient to explain this strong increase.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Previous studies from this lake showed indirect evidence of zooplankton control of phytoplankton (PUG-NETTI and BETTINETTI, 1995;CAMMARANO and MANCA, 1997) and protozoa (CALLIERI et al, 1999;BERTONI et al, 2002) during Daphnia peaks. BOCHDANSKY et al (1995) observed similar increase in both dissolved α-and -glucosidase activities with increase in marine copepods in batch experiments. Small changes in bacterial biomass were not sufficient to explain this strong increase.…”
Section: Discussionsupporting
confidence: 67%
“…Small changes in bacterial biomass were not sufficient to explain this strong increase. Their results showed, moreover, that dissolved α-and -glucosidases were relatively stable and could therefore accumulate during periods of high zooplankton grazing activity (BOCHDANSKY et al, 1995). We believe that such an accumulation of both glucosidases could also be relevant for in bottom water of LPS.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Other than bacteria, also zooplankton and eukaryotes (fungi, diatoms, etc.) have shown to be important producers of extracellular glycosidic activities [20][21][22]. AP is an enzyme involved in the mineralization of organic phosphates with regeneration of phosphate; both bacteria and phytoplankton contribute to its synthesis [23].…”
Section: Editorialmentioning
confidence: 99%